Acceptance of the Use of Pedometers in Individuals with Bipolar Disorder - Danner, Ursula; Macheiner, Tanja; Avian, Alexander; Lackner, Nina; Fellendorf, Frederike; Birner, Armin; Bengesser, Susanne A.; Platzer, Martina; Kapfhammer, Hans-Peter; Reininghaus, Eva (Fortschritte der Neurologie · Psychiatrie, 2017)
Before patients with bipolar disorder (BD) can begin to perform balanced physical activity, they have to overcome many difficulties. The aim of this study was to examine the acceptance of pedometers as a self-assessment tool in people with BD. Patients who participated in an intervention study with body-oriented groups and psychoeducation groups at the Medical University of Graz/ Department of Psychiatry were invited to use pedometers on a daily basis and keep pedometer diaries over a period of 24 weeks. Most of the patients were satisfied with the pedometers and found them helpful for their health. The difficulties in the study were to recruit patients for this exercise trial, their lack of adherence to the programme and a high dropout rate. Out of the 130 invited patients, 41 came to the baseline investigation, 27 of them took part in the group interventions and 14 used pedometers and handed in the pedometer diaries. For clinical practice, specific motivational interventions are recommended to stimulate individuals with BD to engage in regular physical exercise.
Keywords: bipolar disorders; pedometer; physical activity; motivational intervention